Impact of Cardiac Resynchronization Therapy on Left Ventricular Unloading in Patients with Implanted Left Ventricular Assist Devices. Issue 2 (February 2019) - Tehrani, David M.; Adatya, Sirtaz; Grinstein, Jonathan; Rodgers, Daniel; Sarswat, Nitasha; Kim, Gene H.; Raikhelkar, Jayant; Sayer, Gabriel; Uriel, Nir
Abstract : Cardiac resynchronization therapy (CRT) and left ventricular assist devices (LVADs) are common heart failure therapies; however, little is known regarding the concomitant use of these devices. We aim to evaluate unloading differences in LVAD patients with and without active biventricular pacing. Left ventricular assist device patients with and without CRT prospectively underwent ramp hemodynamic/echocardiographic testing. Patients with >95% biventricular pacing comprised the active CRT pacing group; all others (no device, implantable cardioverter defibrillator only, CRT without biventricular pacing) were categorized into the non-CRT pacing group. Invasive hemodynamics and echocardiographic characteristics (left ventricular end-diastolic/systolic diameter and valvular regurgitation) were measured at baseline and at incremental speed changes. Unloading slopes were calculated using linear regression modeling for individual hemodynamics and echocardiographic characteristics across speeds. Among 62 LVAD patients (age 59.6 ± 11.4 years, 60% male), 25 had active CRT pacing. There was no significant difference in echocardiographic or hemodynamic characteristics at baseline or final set speeds between CRT groups. Similarly, no significant differences were noted in the unloading characteristics. In LVAD patients, active biventricular pacing is unlikely to improve echocardiographic or hemodynamic characteristics.